The pig story "tiboi sakkoko"; Storytelling of kinship, memories of the past, and rights to plots of ancestral land in Mentawai - Tulius, Juniator (Wacana, Journal of the Humanities of Indonesia, 2016)
This paper examines some significant elements of the pig story (tiboi sakkoko). This tale contains crucial information about the collective identity, ancestors and historical events affecting particular Mentawai kin-groups. As families do not preserve their culture and traditions in written form, storytellers of kin-groups have narrated the pig story from generation to generation so as to preserve it carefully. In the course of time, storytellers establish particular ways of telling their stories so as to remember the content and plot of the stories easily. Through the pig story, members of kin groups also recollect their ancestral place of origin and plots of ancestral lands. The role of human memory is indispensable to recalling all these important elements. Therefore, this paper analyses memories of the past of different family generations. To achieve its aims, this paper also evaluates the roles of family stories in the culture and traditions of Mentawai society.